Medição do fator de blindagem de cabos coaxiais - Kenedy Marconi Geraldo dos Santos (2011)
The utilization of electro-electronic systems in cars is becoming more and more indispensable to increase the comfort, safety and for the reduction of CO2 emissions. Embedded electro-electronics is increasingly present in vehicles and it comes in addition to telecommunication systems, cellular telephone and Bluetooth RF system, that operate in several frequencies and emit considerable level of electromagnetic fields. Despite the great benefits and services offered by these systems, they may introduce electromagnetic disturbances in the different environments in which they operate. The shielding quality of coaxial cable is an important parameter to guarantee the electromagnetic compatibility of the electro-electronic systems. This concern involves the signal quality in the cable and the correct functioning of the nearby equipments. It would be interesting to detect such a failure as soon aspossible in order to conceive better systems and avoid unnecessary costs. Within this context, this work presents a simplified methodology to validate a virtual measurement in any coaxial cables, through a comparison with a physical experiment.